Overexpression of GA20‐OXIDASE1 impacts plant height, biomass allocation and saccharification efficiency in maize. Issue 3 (7th September 2015) - Voorend, Wannes; Nelissen, Hilde; Vanholme, Ruben; De Vliegher, Alex; Van Breusegem, Frank; Boerjan, Wout; Roldán‐Ruiz, Isabel; Muylle, Hilde; Inzé, Dirk
Summary: Increased biomass yield and quality are of great importance for the improvement of feedstock for the biorefinery. For the production of bioethanol, both stem biomass yield and the conversion efficiency of the polysaccharides in the cell wall to fermentable sugars are of relevance. Increasing the endogenous levels of gibberellic acid (GA) by ectopic expression of GA20‐OXIDASE1 ( GA20‐OX1 ), the rate‐limiting step in GA biosynthesis, is known to affect cell division and cell expansion, resulting in larger plants and organs in several plant species. In this study, we examined biomass yield and quality traits of maize plants overexpressing GA20‐OX1 (GA20‐OX1). GA20‐OX1 plants accumulated more vegetative biomass than control plants in greenhouse experiments, but not consistently over two years of field trials. The stems of these plants were longer but also more slender. Investigation of GA20‐OX1 biomass quality using biochemical analyses showed the presence of more cellulose, lignin and cell wall residue. Cell wall analysis as well as expression analysis of lignin biosynthetic genes in developing stems revealed that cellulose and lignin were deposited earlier in development. Pretreatment of GA20‐OX1 biomass with NaOH resulted in a higher saccharification efficiency per unit of dry weight, in agreement with the higher cellulose content. On the other hand, the cellulose‐to‐glucose conversion was slower upon HCl or hot‐water pretreatment, presumably due to the higher lignin content. This study showed that biomass yield and quality traits can be interconnected, which is important for the development of future breeding strategies to improve lignocellulosic feedstock for bioethanol production.